APPLICATION OF THE CONCEPT OF HALAL AND TAYYIB IN HALAL FOOD CERTIFICATION STANDARDS: POSITIONING MALAYSIA AS A ROLE MODEL - Sazelin, Arif; Ridzwan, Ahmad (2010)

(untitled)
Foods allowed in Islam generally adhere to a strict code of religious dietary law of the lawful (halal) and wholesome (tayyib). Islam outlines two important standards to ensure foods consumed by Muslims are good, quality, pleasant and healthy. Malaysia has moved a step ahead by compiling a globally recognized halal food standard MS 1500. This standard should be read with Malaysian Standard MS 1480, MS 1514 and Halal Food Manual Porcedures. Malaysia is implementing these standards in food processing to ensure the complete application of syari’ah, HACCP as well as GMP. The objectives of this study are to (1) provide an understanding of halal food certification standards in Malaysia and (2) discuss on how the concept of halal and tayyib is applied in these standards. The study adapted a document analysis approach to determine the application of the halal and tayyib concept in halal food certification standards. The documents such as MS 1500, MS 1480, MS 1514 and Halal Food Manual Procedures are the prime sources to be analyzed. To verify the actual application, semi-structured interview is also conducted in this study. The interview involved experts whose been given authorities by the Malaysian government in halal food certification process. The study reveals that Malaysian halal food certification standards is in line with the concept of halal and tayyib as this concept is applied thoroughly and well explained in halal food certification standards. This finding is important so that Malaysia makes the grade to be the role model.